COF-derived cobalt-doped carbon hydrogen storage material and preparation method thereof
By uniformly dispersing the cobalt salt in COFs and carbide reaction, COF@C@Co material is formed, which solves the problem of insufficient hydrogen storage capacity and hydrogen absorption/discharge kinetic performance of COFs, and achieves efficient hydrogen adsorption and release.
Patent Information
- Application Number
- CN202510052799.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-14
- Publication Date
- 2025-03-14
AI Technical Summary
The existing organic frame materials (COFs) have small hydrogen storage capacity under mild conditions and poor hydrogen absorption/discharging kinetics.
By dispersing the cobalt salt evenly within the COFs and carrying out a carbonization reaction, an organic carbon material containing the cobalt active site is formed. The material retains the high specific area and porosity of COFs while also containing cobalt elements to enhance adsorption of hydrogen molecules.
The hydrogen storage capacity and hydrogen absorption/discharge rate are significantly improved, and the maximum hydrogen absorption can reach 3.6 wt.%, improving the hydrogen storage performance of the material.
Smart Images

Figure CN119612442A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of hydrogen storage material preparation, and in particular relates to a COF-derived cobalt-doped carbon hydrogen storage material and a preparation method thereof. Background Art
[0002] Energy storage through hydrogen can achieve a higher energy storage density. As the most likely energy carrier for widespread application, hydrogen energy has the advantages of abundant reserves, diverse sources, clean and pollution-free, and renewable. Based on the various advantages of hydrogen energy, the "hydrogen economy" has developed rapidly. The development of hydrogen energy continues to require excellent hydrogen storage materials, and the research on hydrogen storage materials has become a key factor in the development of the "hydrogen economy".
[0003] Organic framework materials (COFs) are polymers connected by covalent bonds. They form a periodic ordered structure with different organic modules through covalent bonds, and have a three-dimensional pore structure. COFs have many advantages, such as high porosity, low density, large specific surface area, regular pores, adjustable pore size, and diverse and tailorable topological structures, so they have become a research hotspot in the field of hydrogen storage. Although the porous structure of COFs is conducive to the hydrogen absorption process, the COFs porous material itself has low electrical conductivity and insufficient internal hydrogen storage active sites, resulting in a small hydrogen storage capacity under mild conditions and poor hydrogen absorption / desorption kinetics. Therefore, improving the hydrogen storage capacity of COFs and improving their hydrogen absorption / desorption kinetics have become an important direction of current research. Summary of the invention
[0004] The present invention aims to provide a method for preparing an organic framework hydrogen storage material containing carbonized Co metal active sites. An organic carbon material containing cobalt active sites is formed by uniformly dispersing cobalt salt inside COFs and performing a carbonization reaction. The material retains the structural advantages of COFs, namely high specific area and high porosity, and at the same time, the material contains active cobalt elements dispersed in a carbon skeleton matrix. Therefore, the material has a rich pore structure for hydrogen adsorption, and at the same time, the ion-dipole interaction between the cobalt ions and hydrogen molecules inside can enhance the adsorption of hydrogen molecules, thereby improving the hydrogen storage performance of the cobalt-containing organic carbon material, and at the same time, this type of cobalt-containing organic carbon material can also improve the hydrogen absorption / desorption rate.
[0005] The present invention adopts a solvothermal method to prepare COFs, and then carbonizes and modifies the metal sites of the framework by solid-phase carbonization treatment to finally obtain the material. The technical solution of the present invention is as follows:
[0006] In some embodiments of the present application, a COF-derived cobalt-doped carbon hydrogen storage material and a preparation method thereof are provided, comprising the following steps:
[0007] Step 1) N, N-dimethylformamide and trifluoromethanesulfonic acid are measured respectively in a volume ratio of 5 to 20:1, and then 0.01 to 0.015 times the weight of trimesic acid is added to N, N-dimethylformamide under ultrasonic conditions to fully disperse them;
[0008] Step 2) 0.5 to 2 times the weight of p-phenylenediamine of trimesaldehyde is added to the above solution, and after sufficient stirring, the mixture is placed in a hydrothermal kettle and reacted at 120° C. for 48 hours. After the reaction is completed, the solid precipitate is collected by filtration, and the obtained solid precipitate is washed with ethanol, acetone, and water, respectively, and then dried to obtain COF;
[0009] Step 3) Take 0.01 to 0.1 times the weight of cobalt nitrate of COF material, add them to ethanol, stir thoroughly and let stand for 1 hour. Filter and collect the solid precipitate, and after drying the solid, the precursor of COF@Co is obtained;
[0010] Step 4) After the solid obtained in step 3 is fully ground, it is transferred to a tubular furnace protected by argon for calcination, and after keeping warm for a period of time, it is naturally cooled to room temperature and the product is collected;
[0011] Step 5) The product collected in step 4 is added to a dilute acid solution and soaked to remove the nanoparticles and unstable sites, thereby obtaining a COF-derived cobalt-doped carbon hydrogen storage material, named COF@C@Co.
[0012] In some embodiments of the present application, the N, N-dimethylformamide described in step 1 can be replaced by other organic solvents, including N, N-dimethylacetamide, tetrahydrofuran, N-methylpyrrolidone, dioxolane, and 1,4-dichlorohexacyclopentane;
[0013] In some embodiments of the present application, the stirring after adding p-phenylenediamine in step 2 is 1-5 minutes. The reaction temperature may be between 100-150° C., and the reaction time may be between 1-72 hours;
[0014] In some embodiments of the present application, the solid precipitate in step 2 is washed with ethanol, acetone, and water respectively, and washed continuously for 3 to 6 times, and the drying temperature of the solid precipitate in step b is 80 to 100° C., and the drying time is 1 to 10 hours;
[0015] In some embodiments of the present application, the cobalt nitrate in step 3 may be replaced by other cobalt-containing compounds, including one or more of cobalt sulfate, cobalt carbonate, cobalt acetate and their derivatives;
[0016] In some embodiments of the present application, during the calcination process described in step 4, the temperature of the tube furnace is increased to 700-1000°C at a rate of 5-10°C / min, and maintained for 0.5-3 hours after reaching the set temperature;
[0017] In some embodiments of the present application, the dilute acid in step 5 includes one or more of sulfuric acid, hydrochloric acid, and nitric acid. The solution concentration is 1 to 8 mol / L, and the product is immersed in the dilute acid solution for 24 to 48 hours;
[0018] Compared with the prior art, the present invention has the following beneficial effects:
[0019] The preparation method of the present invention is simple, the process is easy to control, the cost is low, and it is suitable for industrial promotion;
[0020] The present invention uses a solid phase carbonization method to functionalize the organic framework, and the carbonization process can be controlled by adjusting reaction conditions such as the heating rate, carbonization temperature, and carbonization time, thereby retaining the ordered porous structure of the organic framework;
[0021] The carbonized COF@Co material has the morphological characteristics of high specific area and high porosity of COFs materials. At the same time, the cobalt element on the framework plays a synergistic role in accelerating the material's hydrogen absorption / desorption process, significantly improving the material's hydrogen storage capacity and hydrogen absorption / desorption rate. Compared with COFs materials that have not been modified with cobalt elements, the maximum hydrogen absorption capacity of the modified COF@C@Co material can reach 3.6wt.%, and the total amount of hydrogen adsorption has been significantly increased. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Various other advantages and benefits will become apparent to those of ordinary skill in the art by reading the detailed description of the preferred embodiments below. The accompanying drawings are only for the purpose of illustrating the preferred embodiments and are not to be considered as limiting the present invention. Moreover, the same reference symbols are used throughout the accompanying drawings to represent the same components. In the accompanying drawings:
[0023] Figure 1 A schematic diagram of an infrared spectrum characterization curve of a COF@C@Co material provided in an embodiment of the present invention;
[0024] Figure 2 A scanning electron microscope schematic diagram of the COF@C@Co material provided in an embodiment of the present invention;
[0025] Figure 3 A schematic diagram of a powder X-ray diffraction characterization curve of the COF@C@Co material provided in an embodiment of the present invention;
[0026] Figure 4 A schematic diagram of a test curve of hydrogen absorption performance of the COF@C@Co material provided in an embodiment of the present invention;
[0027] Figure 5 Schematic diagram of the isothermal adsorption H2 (77K) curve of the COF@C@Co material provided in an embodiment of the present invention. DETAILED DESCRIPTION
[0028] The specific implementation of the present invention is further described in detail below in conjunction with the accompanying drawings and examples. The following examples are used to illustrate the present invention, but are not intended to limit the scope of the present invention.
[0029] In order to better understand the purpose, structure and function of the present invention, the present invention is further described in detail below in conjunction with the accompanying drawings.
[0030] See attached Figure 1-5 As shown, according to some embodiments of the present application, the following preparation steps are performed in sequence:
[0031] (1) Take 25 ml of N,N-dimethylformamide and 3 ml of trifluoromethanesulfonic acid respectively, then add 320 mg of trimesic acid under ultrasonic conditions, and continue ultrasonic treatment at room temperature for 5 min;
[0032] (2) 220 mg of p-phenylenediamine was added to the solution in (1), shaken for 10 min, stirred thoroughly, and then placed in a hydrothermal kettle for reaction at 120° C. for 24 h. The solid precipitate was collected by filtration. The solid precipitate was washed three times with ethanol, acetone, and water, respectively, and then dried in a vacuum oven at 80° C. for 24 h to obtain COF.
[0033] (3) Dissolve 50 mg of cobalt nitrate in 20 ml of ethanol, add 300 mg of COF to the solution, stir for 1.5 hours, filter and rinse with ethanol three times, and dry to obtain COF@Co precursor;
[0034] (4) 250 mg of COF@Co precursor was calcined in a tube furnace. The temperature was raised to 300°C at a rate of 5°C / min and kept at that temperature for 1 hour. The temperature was then raised to 800°C at a rate of 5°C / min and kept at that temperature for 3 hours. The resulting solid was the product COF@C@Co.
[0035] Figure 1 The infrared spectrum characterization curves of the original COF and COF@C@Co materials prepared in the present invention are shown in Figure 1. COF@C@Co basically retains the characteristic peaks of the original COF sample, of which 1578cm-1 and 1238cm-1 belong to the characteristic peaks of C=O and CN, respectively, indicating that the carbonized carbon material still retains the basic chemical structure of the organic framework.
[0036] Figure 2 This is a scanning electron microscope image of the COF@C@Co material prepared in the present invention. It can be seen from the figure that the carbonized material tends to agglomerate into secondary particles with a particle size of about 2-6 microns, and the primary particle size is less than 1 micron. In addition, no obvious inorganic metal salts or oxides were found.
[0037] Figure 3This is the XRD curve of COF@C@Co prepared by the present invention. The XRD spectrum still shows the unique diffraction peak of COF at about 10°, indicating that the carbonized material retains part of the ordered porous structure of COF. In addition, the diffraction peak at about 22° belongs to the stacking peak of the two-dimensional material, which also shows that the carbonized material still retains a good ordered structure. In addition, no other diffraction peaks were found in the XRD spectrum, indicating that the cobalt salt is uniformly dispersed in the carbon material in an amorphous form, which is consistent with the SEM observation results.
[0038] Figure 4 The pore size distribution of COF@C@Co is concentrated in 1-4nm, with a large specific surface area. This shows that the carbonization treatment does not destroy the high crystallinity of the COF material itself, so the structural characteristics of COF with high specific surface area and high porosity can be retained. These characteristics are conducive to enhancing the interaction between hydrogen atoms and cobalt metal active sites and improving the adsorption performance of hydrogen.
[0039] Figure 5 The hydrogen adsorption isotherms of two COF@C@Co with different Co contents at 77K. As can be seen from the figure, within the test range, the COF@C@Co with high Co content has a higher hydrogen storage capacity than the COF@C@Co with low Co content. The pore configurations of these two types of materials are similar, so it is preliminarily speculated that the hydrogen storage performance is mainly affected by the metal content and distribution of the material.
[0040] Through the above technical solution, the technical effects produced in the embodiments of the present application are:
[0041] A cobalt-containing compound is compounded with a COF material with a high nitrogen content at room temperature by a solution method, and then calcined to obtain a cobalt-containing nanoporous carbon material, and the agglomerated cobalt metal nanoparticles are washed out by an acid washing process. COF itself has an ordered porous structure and a high nitrogen content, so the calcined carbon material retains a certain porous structure. This porous carbon coating layer can not only improve the conductivity of the material, but also act as a buffer layer, thereby improving the stability of the hydrogen storage site. The high nitrogen content of COF itself can provide abundant anchoring sites for cobalt atoms and improve its chemical stability. Therefore, the prepared COF-derived cobalt-doped carbon material not only has good hydrogen storage metal site utilization and hydrogen storage activity, but also has good hydrogen storage material reaction kinetics. The material preparation method of the present invention has a simple process, low energy consumption and cost, and is suitable for industrialization.
[0042] In the description of the present application, it should be understood that the terms "center", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", etc., indicating orientations or positional relationships, are based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present application and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as a limitation on the present application.
[0043] The terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Thus, a feature defined as "first" or "second" may explicitly or implicitly include one or more of the features. In the description of this application, unless otherwise specified, "plurality" means two or more.
[0044] In the description of this application, it should be noted that, unless otherwise clearly specified and limited, the terms "installed", "connected", and "connected" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be indirectly connected through an intermediate medium, or it can be the internal communication of two components. For ordinary technicians in this field, the specific meanings of the above terms in this application can be understood according to specific circumstances.
[0045] In this specification, each embodiment is described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the embodiments can be referred to each other. For the device disclosed in the embodiment, since it corresponds to the method disclosed in the embodiment, the description is relatively simple, and the relevant parts can be referred to the method part.
[0046] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A COF-derived cobalt-doped carbon hydrogen storage material and a method for preparing the same, characterized in that: The following steps are involved: Step 1) weighing an appropriate amount of an organic solvent and trifluoromethanesulfonic acid, mixing them, and weighing an appropriate amount of trimesic acid, and dispersing them uniformly with the organic solvent and trifluoromethanesulfonic acid under ultrasonic conditions to obtain a mixed solution A; Step 2) adding an appropriate amount of p-phenylenediamine to the mixed solution A, stirring sufficiently, placing the mixed solution in a hydrothermal reactor and reacting at 120° C. for 48 hours. After the reaction is completed, filtering and collecting the solid precipitate, and washing the precipitate to obtain COF; Step 3) COF and an appropriate amount of a cobalt-containing compound are added to ethanol, stirred thoroughly, and allowed to stand for 1 hour, the precipitate is separated, and the precipitate is subsequently treated to obtain a COF@Co precursor; Step 4) After the COF@Co precursor is fully ground, it is transferred to an argon-protected tubular furnace for calcination, and after being kept warm for a period of time, it is naturally cooled to room temperature and the product is collected; Step 5) The product collected in step 4 is added to a dilute acid solution and soaked to remove the nanoparticles and unstable sites, thereby obtaining a COF-derived cobalt-doped carbon hydrogen storage material, named COF@C@Co.
2. The COF-derived cobalt-doped carbon hydrogen storage material and preparation method thereof according to claim 1, characterized in that: The organic solvent in step 1 is one of: N, N-dimethylformamide, N, N-dimethylacetamide, tetrahydrofuran, N-methylpyrrolidone, dioxolane, and 1,4-dichlorohexacyclopentane.
3. The COF-derived cobalt-doped carbon hydrogen storage material and preparation method thereof according to claim 1, characterized in that: The volume ratio of the organic solvent to trifluoromethanesulfonic acid in step 1 is 5 to 20:1; wherein the weight of trimesaldehyde is 0.01 to 0.015 times the weight of the organic solvent.
4. The COF-derived cobalt-doped carbon hydrogen storage material and the preparation method thereof according to claim 1, characterized in that: The weight of p-phenylenediamine in step 2 is 0.5 to 2.0 times the weight of trimesaldehyde.
5. The COF-derived cobalt-doped carbon hydrogen storage material and the preparation method thereof according to claim 1, characterized in that: The cleaning treatment in step 2 is to wash the precipitate with ethanol, acetone and water for 3 to 6 consecutive times, and then dry the precipitate at a drying temperature of 80 to 100° C. for 1 to 10 hours.
6. The COF-derived cobalt-doped carbon hydrogen storage material and the preparation method thereof according to claim 1, characterized in that: The cobalt-containing compound in step 3 is one or a combination of cobalt nitrate, cobalt sulfate, cobalt carbonate, cobalt acetate and their derivatives, wherein the weight of the cobalt-containing compound is 0.01 to 0.1 times the weight of COF.
7. The COF-derived cobalt-doped carbon hydrogen storage material and the preparation method thereof according to claim 1, characterized in that: During the calcination process in step 4, the temperature of the tubular furnace is increased to 700-1000° C. at a rate of 5-10° C. / min, and maintained for 0.5-3 hours after reaching the set temperature.
8. The COF-derived cobalt-doped carbon hydrogen storage material and the preparation method thereof according to claim 1, characterized in that: The dilute acid in step 5 is one or a combination of sulfuric acid, hydrochloric acid and nitric acid, wherein the concentration of the dilute acid is 1 to 8 mol / L, and the product in step 4 is immersed in the dilute acid for 24 to 48 hours.